Pengaruh Problem Based Learning Dengan Strategi “MURDER” Terhadap Kemampuan Pemahaman Konsep Matematis Siswa - Yeyen Sayekti (AlphaMath : Journal of Mathematics Education, 2019)
This study aimed to determine the effectiveness of Problem Based Learning with MURDER strategy on students mathematical concept understanding ability in SMP Negeri 2 Sokaraja Academic Year 2018/2019. The method used was experimental research. Population in the study were the eighth-grade students of SMP Negeri 2 Sokaraja. The sampling was done by cluster random sampling technique; class VIII A as an experimental class treated by using Problem Based Learning with MURDER strategy and class VIII B as a class controls that used conventional learning. That instrument used was a post test problem that measures the ability to understand mathematical concepts. Based on the result of the t-test analysis with the help of SPSS 25.0, the Sig (2-tailed) = 0.015. Because it uses the right-side test, the Sig (2tailed) value is divided by 2 so that it gets 0.0075.With α = 0.05 then the value of Sig (2-tailed) meant that Ho rejected. This meant that the ability of students to understand mathematical concepts who were exposed by Problem Based Learning with MURDER strategy were more improved from those who only follow conventional learning. Therefore, it could be concluded that Problem Based Learning with MURDER strategy affected the mathematical concept of understanding ability.